Effectiveness of Katuk Leaf (Sauropus Androgynus) Consumption on the Smoothness of Milk Production in Primpara Breastfeeding Mothers - Marchatus Soleha; Vika Tri Zelharsandy; Wika Sepiwiryanti; Indah Lestari (Lentera Perawat, 2024)
The attention of mothers and health workers must be pain to breasfeeding process is carried coret correctly. Breastfeeding promotes a bond of love and affection between mother and newborn. Breast milk production can be increased by eating katuk leaves as they contain alkaloids and stereols that can increase the flow of breast milk. Katuk leaves also contain vitamins A, B1, C, tannins, alkaloid saponins. The aim of this study was to find out the effectiveness of eating katuk leaves in smoothing milk production in first-time lactating mothers. This type of research was quantitative and quasi-experimental designs using  Posttest With Control Group. The population of this study consisted of all primiparous nursing mothers of PMB Yosephine in Palembang, up to 30 people. The samples of the study were 15 respondents ate katuk leaves and 15 respondents did not eat katuk leaves. The analysis used was the paired sample t-test. The results of the study of the milk production of mothers who did not use katuk leaves were that 14 respondents had less milk production  (93.3%) and those who used katuk leaves had a lot of milk production (100%). the  paired sample t-test results showed  p = 0.000 where Ha was accepted, which means that katuk leaves are effective for consistent milk production in 2023 PMB yosephine Palembang City lactating mothers for the first time.